Geopolítica do etanol: soberania energética e projeção internacional do Brasil (1930-2015) - Elisa Pinheiro de Freitas; Antonio Marcos Roseira; Mateus de Almeida Prado Sampaio (Confins)
Alcohol production is based on Brazil's primary exporting history during the colonial, imperial and republican eras. The economic and scientific-technological development of this energy matrix in the twentieth century is intertwined with the establishment of a geopolitical rationality and the definition of the main Brazilian strategic interests. Two major periods are distinguished in this analyses. In the developmentalism period (1930-1980), biofuel was important to energy sovereignty policies. Following a hiatus marked by a crisis in the sugar and ethanol sector in the 1990s, ethanol become central in the country's international projection policies during the 2000s. Taken together, the history of this energy matrix demonstrates its importance for national development.Ethanol; Energy Geopolitics; Sovereignty; International Projection; Brazil.